Use of complementary and alternative medicine: Prevalence and health literacy among patients attending a Health Centre in Universiti Teknologi MARA Selangor / Siti Khuzaimah Ahmad Sharoni, Syahirah Robani, Syuhaidah Aiza Zaini - Ahmad Sharoni, Siti Khuzaimah; Robani, Syahirah; Zaini, Syuhaidah Aiza (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The used of Complementary and Alternative Medicine (CAM) has gained worldwide trust in developed and developing country. CAM used is associated with self-care decisions making in obtaining treatment and various benefits and possible adverse effects. Although CAM used is popular among Malaysian users, however, limited published studies related to their health literacy of CAM among this population. This study determines the prevalence and health literacy of CAMs among patients in a Health Centre, Universiti Teknologi MARA (UiTM) Selangor. A cross-sectional study was conducted at a Health Centre, UiTM Selangor from April 2019 to May 2019. A questionnaire consisting of demographic data, health status and the Montana State University Complementary and Alternative Medicine Health Literacy Scale was distributed to a total of 306 respondents. Descriptive analysis and inferential analysis were analysed for the study. The result shows the prevalence of CAM used was 35.6% and 27% of participants reported feeling satisfied with the CAM used. This study also reported a high literacy level of CAM among patients attending the Health Centre (Mean=61.784, SD=5.403). There was a weak positive relationship between health literacy and age (rs=0.199, p<0.001). These study also found that health literacy for female is statistically significantly higher (Mean=62.053, SD=5.261) than male (Mean=60.140, SD=6.006); [t(304)=-2.166,p=0.031]. These results suggest female gender, being older, had better health literacy regarding CAM. This emphasizes that there is a need for the healthcare provider to keep on assessing and educate their patients especially among men and younger population with adequate information regarding CAM use.